BS EN 61169-21. Radio-frequency connectors. Part 21. Two types of radio-frequency connectors with inner diameter of outer conductor 9.5 mm (0.374 in) with different versions of screw coupling. Characteristic impedance 50 ohms (Types SC-A and SC-B) (14th November 2020) - British Standards Institution
No abstract available